Experimental confirmation of some factors influencing dynamic concrete compressive strengths in high-speed impact tests - Hao, Yifei; Hao, Hong; Jiang, G.; Zhou, Y. (Pergamon- Elservier, 2013)
This paper reports probably the first systematic experimental investigation of the influences of lateral inertia confinement, end friction confinement and aggregates in high-speed impact tests on dynamic compressive properties of concrete. The influences of the concerned factors on the dynamic increase factor (DIF) are discussed. The proposed DIF relations in Hao and Hao [36] are verified by the experimental data in this study. The results confirm the observations made before based on numerical simulations that lateral inertia confinement effect is dependent on the specimen diameter and strain rate. The influences of aggregate size and volume to DIF are considerable, and aggregates cannot be neglected in experimental or numerical studies. It also confirms that the end friction confinement effect is sensitive to the specimen geometry and strain rate. The equation proposed in Hao et al. [40] based on numerical simulations satisfactorily removes the friction confinement effect on the DIF of concrete material strength obtained in impact test.